2018
DOI: 10.19090/pp.2018.3.365-384
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and Work Burnout From the Rebt Perspective: A Short–term Prospective Study

Abstract: The main objective of the study was to test REBT model of emo- tion in prediction of burnout. It was hypothesized that dysfunc- tional negative emotions (DNE) would positively predict burnout, positive emotions (PE) would negatively predict buronut, while functional negative emotions (FNE) were hypothesized to be un- correlated to burnout. To test those assumptions, a short‒term, 12 week prospective study was carried out (three measurements, with the interval of 6 weeks). A sample of 197 employees took part in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The effectiveness of the REBT group in overcoming boredom was also supported by Popov et al (2018) in their research entitled 'Emotions and Work Burnout from the REBT Perspective: A Short-Term Prospective Study'. The results of their study showed that emotion is the most obvious manifestation of fatigue or saturation.The instrument used in their study is the WB Scale (Work Burnout Scale).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The effectiveness of the REBT group in overcoming boredom was also supported by Popov et al (2018) in their research entitled 'Emotions and Work Burnout from the REBT Perspective: A Short-Term Prospective Study'. The results of their study showed that emotion is the most obvious manifestation of fatigue or saturation.The instrument used in their study is the WB Scale (Work Burnout Scale).…”
Section: Discussionmentioning
confidence: 86%
“…The results of the research by Popov, Jeli', Rakovi', & Matanovi' (2018) titled 'Emotions and Work Burnout from the REBT Perspective: A Short-Term Prospective Study', showed that emotional experiences have a greater effect on burnout and this burnout leads to anxiety, anger, worry, depression, sadness and other negative feelings.…”
Section: Discussionmentioning
confidence: 99%